2018
DOI: 10.3389/fimmu.2018.00723
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived Extracellular Vesicles Induce Long-Lasting Immunity Against Hepatitis C Virus Which Is Blunted by Polyunsaturated Fatty Acids

Abstract: Extracellular vesicles (EVs) are increasingly recognized as important mediators of intercellular communication. In this study, we aimed to further characterize the role of macrophage-derived EVs in immune responses against hepatitis C virus (HCV) and the potential of polyunsaturated fatty acids (PUFAs) to modulate this modality of innate immunity. To this end, EVs were isolated from interferon-stimulated macrophage cultures or from serum of patients with acute or chronic hepatitis C. EVs were characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 32 publications
1
63
0
Order By: Relevance
“…Similarly, adipose tissue macrophage‐derived EVs can influence systemic insulin resistance in obesity . Macrophage‐derived EVs can influence anti‐hepatitis C immune responses and placental inflammatory responses . Adipose tissue expansion and inflammation are a component of obesity‐associated metabolic syndrome in our mouse dietary model and in humans with NASH .…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, adipose tissue macrophage‐derived EVs can influence systemic insulin resistance in obesity . Macrophage‐derived EVs can influence anti‐hepatitis C immune responses and placental inflammatory responses . Adipose tissue expansion and inflammation are a component of obesity‐associated metabolic syndrome in our mouse dietary model and in humans with NASH .…”
Section: Discussionmentioning
confidence: 96%
“…Long-chain polyunsaturated fatty acids (PUFAs) are important mediators of inflammation and adaptive immune responses. 31 Omega-3…”
Section: Omega-3 Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…They are precursors of resolvins/protectins and prostaglandins/leukotrienes, respectively. 31 Begin et al 32 had studied plasma lipids levels in patients with AIDS and had found that a selective and specific lack of the long-chain PUFAs of omega-3 series, which are found in high concentrations in fish oils. In addition, protectin D1, the omega-3 PUFA-derived lipid mediator, could markedly attenuate influenza virus replication via RNA export machinery.…”
Section: Omega-3 Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…Interestingly, it seems that macrophages may have certain mechanisms to mediate the release pattern and synergistic effects of cytokines and EVs in response to infections. For example, macrophages orchestrate a fast but short-lasting antiviral state by secreting cytokines during HCV infection, while their EVs induce a late but long-lasting inhibition on HCV replication in hepatocytes with sub-genomic HCV replicons 124 . These studies suggest that Mφ-EVs may boost the anti-infective immune response by delivering viral materials or therapeutic molecules.…”
Section: Therapeutic Roles Of Mφ-evs In Diseasesmentioning
confidence: 99%